The Urgency of a Deep Learning Approach in Strengthening the Implementation of the Kurikulum Merdeka in Primary Schools - Jauharah, Nadila; Mirza Aulia; Vera (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
The deep learning approach in education emphasizes deep conceptual understanding, active student engagement, and the integration of contextual knowledge. This study aims to analyze the urgency and potential synergy between deep learning and the Kurikulum Merdeka in strengthening the quality of primary education in Indonesia. A qualitative method with a literature review was employed to gain an in-depth understanding from relevant sources. The study population consisted of literature on the Kurikulum Merdeka, deep learning, and Indonesian primary education, with a purposive sample drawn from credible sources published between 2021 and 2025. Documentation instruments and qualitative content analysis were used to identify themes and conceptual relationships. The results indicate that integrating deep learning into the Kurikulum Merdeka fosters meaningful, active, and contextual learning that strengthens character development and 21st-century competencies. However, challenges remain, particularly regarding teacher readiness and infrastructure. In conclusion, this approach is crucial for reinforcing the implementation of the Kurikulum Merdeka, requiring continuous teacher training and policy support to ensure equitable resource distribution.